ANALISIS DAYA SAING KOMODITI EKSPOR UNGGULAN INDONESIA DI PASAR INTERNASIONAL - Farid Ustriaji (Jurnal Ekonomi Pembangunan, 2016)
Research aimed to investigate the growth, contribution, and also the competitiveness of excellent commodity exports comprising textile and textile-based products, electronics, rubber, rubber-palmed products and oil-palmed products, forest products, footwear, automotive, shrimp, cocoa, and coffee. In fact, this research revealed that: Some of those commodity exports exhibited the significant increase: The oil-palmed products were the most greatly contributive amongst commodity exports of which accumulation achieved first and total of exports reached during 2010-2014: The RCA formulation of oil-palmed products, footwear, cacao, coffee, rubber, and textile in 2010-2014 commodity exports had excellent competitiveness throughout international world.